Accuracy of multiecho magnitude‐based MRI (M‐MRI) for estimation of hepatic proton density fat fraction (PDFF) in children. Issue 5 (3rd April 2015) - Zand, Kevin A.; Shah, Amol; Heba, Elhamy; Wolfson, Tanya; Hamilton, Gavin; Lam, Jessica; Chen, Joshua; Hooker, Jonathan C.; Gamst, Anthony C.; Middleton, Michael S.; Schwimmer, Jeffrey B.; Sirlin, Claude B.
<x xml:space="preserve">Abstract</x> Purpose To assess accuracy of magnitude‐based magnetic resonance imaging (M‐MRI) in children to estimate hepatic proton density fat fraction (PDFF) using two to six echoes, with magnetic resonance spectroscopy (MRS) ‐measured PDFF as a reference standard. Methods This was an IRB‐approved, HIPAA‐compliant, single‐center, cross‐sectional, retrospective analysis of data collected prospectively between 2008 and 2013 in children with known or suspected nonalcoholic fatty liver disease (NAFLD). Two hundred eighty‐six children (8–20 [mean 14.2 ± 2.5] years; 182 boys) underwent same‐day MRS and M‐MRI. Unenhanced two‐dimensional axial spoiled gradient‐recalled‐echo images at six echo times were obtained at 3T after a single low‐flip‐angle (10°) excitation with ≥ 120‐ms recovery time. Hepatic PDFF was estimated using the first two, three, four, five, and all six echoes. For each number of echoes, accuracy of M‐MRI to estimate PDFF was assessed by linear regression with MRS‐PDFF as reference standard. Accuracy metrics were regression intercept, slope, average bias, and R2. Results MRS‐PDFF ranged from 0.2–40.4% (mean 13.1 ± 9.8%). Using three to six echoes, regression intercept, slope, and average bias were 0.46–0.96%, 0.99–1.01, and 0.57–0.89%, respectively. Using two echoes, these values were 2.98%, 0.97, and 2.72%, respectively. R2 ranged 0.98–0.99 for all methods. Conclusion Using three to six echoes, M‐MRI has high accuracy for hepatic PDFF estimation in children. J. Magn. Reson. Imaging 2015;42:1223–1232.